Understanding the links between agriculture and health: Agriculture, Environment, and Health: Toward Sustainable Solutions - Nugent, Rachel; Drescher, Axel (International Food Policy Research Institute, 2006)
Agricultural production relies on environmental services to transform raw inputs into the nutritious and diverse food that humans rely on for survival. Although the practice of agriculture is essential for human health, careless and inappropriate agricultural practices can degrade and contaminate natural resources and in so doing, harm human health. Modified agricultural practices can help mitigate these problems. This brief provides an overview of the linkages between agriculture, environment, and health, some of which are dealt with in more detail in other briefs in this series.